Diagnóstico para la implementación del proyecto Mujeres Contando en Diagnóstico para la implementación del proyecto Mujeres contando en voz alta en la ciudad de Quito Voz Alta en la ciudad de Quito - Torres Bueno, María Belén (2014)
The present investigation obeys to satisfying more than one need. Nowadays nobody can close the eyes face to a bitter reality which has nothing to do with gender equality , so much world level as in our country, though often they are slightly significant and very publicized, which is making in the group a false perception on the reality of the problem, in respect about using the Internet as channel of communication has the advantage of not being a channel regulated by any law (at least in our country) though, at present Law of Telecommunications sanctions whom misinforms or issues slanderous declarations for the communications media. At present it allows to come in our country to 35,1 % (INEC, 2012) of the population, a hearing that demands updated and reliable information which tries to come near with the message of the project " Women telling loudly " it originated in Colombia and that it seeks to announce the activities of the groups involved in the defense of the gender equity, the human rights and not violence against the woman.